Problemy samodzielności decyzyjnej przedsiębiorstwa uspołecznionego - Dąbrowski, Zdzisław (Wydział Prawa i Administracji UAM, 1987)
The article aims at presenting basic problems of decision-making independence of an enterprise arising in connection with the present (instituted in 1982) economic reform which opened new and hitherto unknown possibilities for an enterprise to shape independently its own activity at short and long range. The considerations are laid in a historical background, helping to accentuate innovatory and progressive conceptions of the reform and to expose the facts of retaining or rejecting some solutions introduced by previous reforms. The starting point has been provided by the thesis about limied decision-making independence of an enterprise as long as the national economy functions under the conditions of socialized basic means of production and the active role of the central plan. However, the above does not settle explicitly the question of the range and types of independence; the latter may be shapd in various ways. Accepting fully an extensive, and as broad as possible, independence of an enterprise in current and developmental matters, the author carried out the detailed analysis of three main decision-making spheres: 1) the decisions concerning production and exploitation, 2) the decisions concerning supplies and sales, 3) the decisions concerning property and income. The results of the analysis are to inform the management of new opportunities and prerogatives of its decision-making activity and of the problems to be autonomically overcome and solved by means of decision-making measures.
The Problems of Decision-Making Independence of a Socialized Enterprise